Characterization of rhizobia indicated for inoculant production using 16S rRNA partial sequencing - Toledo, Bethânia Figueiredo Barbosa de; Marcondes, Jackson; Lemos, Eliana Gertrudes de Macedo (Pesquisa Agropecuaria Brasileira, 2010)
The aim of this work was to compare the partial sequences of 16S rRNA gene of rhizobia strain patterns already classified with strains recommended for the production of inoculants in Brazil, in order to verify the reliability of partial sequencing of the gene for the purpose of rapid identification of strains. (PCR) sequencing using primers on the coding region of the 16S rRNA gene among the bacteria studied was conducted. The results were analyzed by consulting the nucleotides' similarity based on Basic Local Alignment Search Tool (Blastn) and by interpreting the phylogenetic trees generated by bioinformatic tools. The taxonomic classification of Semia strains recommended for legume inoculation based on morphological properties and host specificity was not confirmed in all strains. The similarity of the Blastn consultation by partial sequencing of the gene found in strains studied is consistent with the classification proposed by the construction of a phylogenetic tree of sequences of strains in most cases.
Keywords: Bradyrhizobium; Rhizobium; phylogeny